PERAN GURU PENDIDIKAN AGAMA KATOLIK DALAM MEMBENTUK KARAKTER DISIPLIN PESERTA DIDIK DI SEKOLAH MENENGAH ATAS SWASTA KATOLIK 2 KABANJAHE - Sembiring, Mimpin; Sinuraya, Arisinta (STP St. Bonaventura Medan, 2022)
The aim of this research is to determine the role of Catholic Religious Education Teachers in shaping the disciplined character of Class XI students at Kabanjahe 2 Catholic Private High School. In achieving this goal, research was carried out at Kabanjahe 2 Catholic Private High School. The informants in this research were religious teachers, school principals and students. Teachers have a role as motivators, as role models and as managers of learning. The teacher referred to in this research is a Catholic religious education teacher. Researchers use qualitative research methods. The data collection technique uses 3 (three) activities, namely observation, interviews and documentation. Based on field results, the religion teacher at Private Catholic High School 2 Kabanjahe carries out his role as a teacher, so that he can shape the disciplined character of students. This is characterized by students who obey the rules, do their assignments on time and are loyal in following the teaching and learning process in class.